Efek Penyuluhan terhadap Pengetahuan Tentang Dampak Pernikahan Usia Dini pada Remaja di Dusun Pancor Desa Guntur Macan Kecamatan Gunung Sari Kabupaten Lombok Barat, Nusa Tenggara Barat - Khairil Pahmi; Irni Dwi Astiti; Bq Safinatunnaja; Rizka Yuliana Saputri; Ali Akbar Rafsanjani; Difa Udiana (PT.Mantaya Idea Batara, 2022)
Adolescence is a transitional period marked by physical, emotional and psychological changes. Teenagers are the next generation of the nation, where the good or bad of a nation in the future depends on how the condition of the youth of the younger generation is today. Early marriage in Indonesia is still relatively high. Data from Indonesia shows that around 61,000 children are married at the age of under 15 years and more than 1 million children are married at the age of less than 18 years. The method used in community service with the theme of education Community empowerment activities regarding the provision of health education on the impact of early marriage on adolescents are carried out on Friday, March 25, 2021, from 13.00 to 15.00 at the Posyandu Pancor Hamlet, Guntur Macan Village, West Lombok. demonstration of the impact of film screening on early marriage on adolescents. Based on the distribution of respondents based on the level of education from the results of research that has been done that the education level of the most respondents is junior high school, which is 8 respondents (53.33%). There is an effect of counseling on knowledge about the impact of early marriage on adolescents in Pancor Hamlet, Guntur Macan Village, Gunung Sari District, West Lombok Regency, NTB (p=0.000)